Strategi Public Relations Startup Ngampooz Melalui Program Ngampooz Internship - Fatona, Anindya; Sutarjo, Moch. Armien Syifaa (Jurnal Pustaka Komunikasi, 2025)
This research discusses the Public Relations (PR) strategy of the Ngampooz Startup through the Ngampooz Internship program. The aim is to understand and analyze the strategic steps taken by Ngampooz in maintaining business and building long-term relationships with its public. This research uses a qualitative approach with a case study method, involving interviews, documentation, and observation. The research refers to the Cutlip, Center, and Broom PR strategy model, which involves Defining the Problem, Planning and Programming, Taking Action and Communication, and Evaluating the Program. The research results show that Ngampooz is effective in carrying out these processes through the Ngampooz Internship. In defining the problem, Ngampooz carried out opportunity analysis, internal brainstorming, and idea generation. The planning stage involves planning goals, objectives, program packaging strategies, and program information delivery strategies. The process continues with action and communication via Instagram and company networking. Program evaluation is carried out through monthly monitoring. The research results confirm that Ngampooz's PR strategy through the Ngampooz Internship has succeeded in building public trust and long-term relationships. With structured and proactive steps, Ngampooz creates a positive impact on the company's communications and interactions with its public.